2018
DOI: 10.5943/mycosphere/9/5/6
|View full text |Cite
|
Sign up to set email alerts
|

Current status of global Ganoderma cultivation, products, industry and market

Abstract: Among many traditional medicines, Ganoderma has been used in Asian countries for over two millennia as a traditional medicine for maintaining vivacity and longevity. Research on various metabolic activities of Ganoderma have been performed both in vitro and in vivo studies. However, it is debatable whether Ganoderma is a food supplement for health maintenance or a therapeutic "drug" for medical purposes. Over the past two decades, the Ganoderma industry has developed greatly and today offers thousands of produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 22 publications
0
61
0
3
Order By: Relevance
“…31 In recent years, there has been an increasing concern about the quality of reishi products. 32 In an analysis of polysaccharide and triterpene profiles, Wu et al found that only 26.3 % of the Ganoderma lucidum supplements were in accordance with their labels. 18 This study also found significant variations in the β-glucan content among reishi supplements.…”
Section: Resultsmentioning
confidence: 99%
“…31 In recent years, there has been an increasing concern about the quality of reishi products. 32 In an analysis of polysaccharide and triterpene profiles, Wu et al found that only 26.3 % of the Ganoderma lucidum supplements were in accordance with their labels. 18 This study also found significant variations in the β-glucan content among reishi supplements.…”
Section: Resultsmentioning
confidence: 99%
“…Current methods used in commercial production of Ganoderma, include wood log, tree stump, sawdust bag, short blocks of basswood (from the tree genus Tilia, known as Lime or Linden in Europe) and bottle procedures (Hapuarachchi et al, 2018). Mycelial growth, fruiting and development of fruit bodies require specific nutritional factors and environmental conditions (Zhou et al, 2017).…”
Section: Development and Morphogenesismentioning
confidence: 99%
“…Modern studies have shown that G. lucidum polysaccharides (GLPs) and Ganoderma triterpenoids (GTs) which improve immunity and exert antiaging effects are the main contributors to the traditional pharmacological activities of G. lucidum. G. lucidum has been included in the Chinese Pharmacopoeia and in the American Herbal Pharmacopoeia and Therapeutic Compendium (Hapuarachchi et al 2018).…”
Section: Traditional Uses Of G Lucidum In Chinamentioning
confidence: 99%